TRANSFORMASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM MELALUI TEKNOLOGI KECERDASAN BUATAN - Irma Oihu; Basri; Muhammad Ridwan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the application of artificial intelligence technology in the learning process of Islamic Religious Education students and to explore students' experiences and perceptions regarding its use in academic activities. This study employed a descriptive qualitative approach with 29 eighth-semester students of the Islamic Religious Education Study Program as research subjects, selected through cluster random sampling technique. Data were collected through observation, semi-structured interviews, and documentation, then analyzed using the Miles and Huberman model through the stages of data condensation, data presentation, and conclusion drawing. Data validity was ensured through source triangulation and technique triangulation. The findings reveal that students have actively and comprehensively utilized AI across various courses, both general and Islamic studies, using platforms such as ChatGPT, Gemini, and Meta AI to understand course materials, complete assignments, and compose academic works. Students perceive AI as a tool that provides convenience and learning efficiency, while also contributing to improved academic achievement. However, excessive use potentially leads to dependency and weakens critical thinking skills. This study affirms that AI should be utilized wisely as a learning support tool that aligns with the values of Islamic education.